Histological profiling of the extracellular matrix of streptozotocin-induced diabetic nephropathy in experimental mice and rats, an analytical study - Anas K. Al Makhzoomi (Iraqi Journal of Veterinary Sciences)
Diabetic nephropathy (DN) is characterized by dysfunction and a complication of the extracellular matrix (ECM) with an abnormal pattern of Glycosaminoglycan (GAG) synthesis. The present work also intends to monitor and analyse the ECM and GAG alterations responsible for the development of DN by employing streptozotocin (STZ)-induced diabetic models in albino mice. It also evaluates the effectiveness of pharmacological strategies in treating GAG changes. According to the PRISMA guidelines, the articles published between 1992 and 2024 in PubMed, Scopus, Science Direct, and Google Scholar were analyzed studies (n=18) that used experimental models of DN with histological analysis of ECM, which included GAGs only. Staining methods like Alcian blue and Periodic Acid -Schiff (PAS) were used to assess GAG content quantitatively. Some findings that were associated with diabetic conditions, including increased ECM deposition, thickening of the glomerular basement membrane, mesangial hypertrophy, and proteinuria, were elaborated. It was found that such structural alterations may cause GAG dysregulation and lead to renal fibrosis. The effects of propolis and human Mesenchymal stem cells (MSCs) on GAG balance, ECM deposition, and renal function of diabetic models were found. Aberrant GAG expression has also been found to affect the progression of DN directly.